Trade-offs between inflation targeting and financial stability objectives: Drivers of gains from coordinating monetary and macroprudential policies - Jessica Roldán-Pe\~na; Mauricio Torres-Ferro; Alberto Torres García (Banco de México, 2017)
This paper studies the trade-offs that can arise between inflation targeting and financial stability objectives. We use a simple framework to conduct macroeconomic policy analysis under three strategies: (1) a benchmark case where monetary policy pursues traditional price stability objectives; (2) monetary policy leaning against the wind; and (3) a case of policy coordination between monetary and macroprudential instruments. We find that, under certain circumstances, having financial stability objectives as an additional macroeconomic policy increases the volatility of inflation. We identify cases in which the tradeoffs in terms of macroeconomic volatility between policy objectives create scope for improvement when monetary and macroprudential policies are coordinated. These improvements are generally larger when financial shocks are the main driver of macroeconomic fluctuations.
Keywords: E44; E52; E61; G28; 330; Price and Financial Stability; Leaning Against the Wind; Monetary and Macroprudential Policy Coordination